HUBUNGAN BERAT BADAN LAHIR DENGAN KEJADIAN RUPTUR PERINEUM PADA IBU PRIMIPARA - Hestri Norhapifah; Ida Hayati; Yosi Arum Ariningtyas (ITKES Wiyata Husada Samarinda, 2018)
Perineal laceration is an indirect cause of maternal deaths worldwide due to lead to the occurrence of postpartum haemorrhage. Controlling the release of the baby's head is gradually and carefully to reduce excessive strain (tear) in the vagina and perineum. The size of the average head depending on the size (weight) of the fetus (Purposari, 2010). The method in this study using analytic survey with cross sectional approach. The sampling technique consecutive sample with a sample of 62 women giving birth the first time. Data was analyzed using bivariate analysis stage using chi-square test. Results correlation with birth weight rupture perineum with bivariate analysis results obtained value p-value of 0.00 and RR 9.52 (95% CI: 1.37 to 66.0) which means that birth weight <3500 g had a 9.52 times greater risk for not rupture compared with birth weight ≥ 3500 g.